2021
DOI: 10.3389/fsufs.2021.681684
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds From Brewer's Spent Grains: Toward Green Recovery Methods and Applications in the Cosmetic Industry

Abstract: Brewers' spent grain (BSG) is the main by-product derived from the brewing industry, where it accounts for 85% of the total waste generated. The total annual production worldwide of this waste is 39 million tons. This lignocellulosic material is traditionally used as cattle feed and sold at a low retail price (~USD 45.00 per ton). However, efforts for the revalorization of this by-product are emerging since research has established that it can be used as a low-cost source of bioactive molecules and commodity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…The presence of phenolics could be attributed to the use of a mixture of aqueous ethanol and alkali for extraction. Previous studies have successfully shown that phenolic compounds can be extracted using alkalis ( Meneses et al, 2013 , Qin et al, 2019 ) and aqueous ethanol ( Meneses et al, 2013 , Qin et al, 2019 ), and the majority of phenolic acids in BSG are ferulic acid and p-coumaric acid ( Macias-Garbett et al, 2021 ). The greater amount of phenolics in the fermented extract is supported by earlier literature since fermentation breaks down the cell walls and enzymatic activities liberate the bound phenolic compounds ( Adebo and Gabriela Medina-Meza, 2020 , Cooray and Chen, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of phenolics could be attributed to the use of a mixture of aqueous ethanol and alkali for extraction. Previous studies have successfully shown that phenolic compounds can be extracted using alkalis ( Meneses et al, 2013 , Qin et al, 2019 ) and aqueous ethanol ( Meneses et al, 2013 , Qin et al, 2019 ), and the majority of phenolic acids in BSG are ferulic acid and p-coumaric acid ( Macias-Garbett et al, 2021 ). The greater amount of phenolics in the fermented extract is supported by earlier literature since fermentation breaks down the cell walls and enzymatic activities liberate the bound phenolic compounds ( Adebo and Gabriela Medina-Meza, 2020 , Cooray and Chen, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the brewing industry, a large quantity of waste is produced, of which 85% of the total waste comes from brewers’ spent grains (BSG). Annually, an estimated 39 million tons of BSG is generated worldwide ( Macias-Garbett et al, 2021 ). Given the difficulty in preserving these residues due to its high moisture content and complex composition, excess BSG is likely to be disposed of or used as cattle feed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, Guido et al showed that some phenolic compounds such as cinnamic and benzoic acids, due to their high polarity, could not be completely extracted by using pure solvents, and therefore, the use of mixtures such as acetone–water and alcohol–water are highly recommended [ 38 ]. Besides the phenolic compound recovery, the SLE technique has certain drawbacks, such as the high volume of the required solvents and long extraction time [ 8 , 38 ]. The method’s downsides include the restricted use of solvents due to food safety concerns, as well as the risk of target component degrading [ 38 ].…”
Section: Conventional Extraction Methodsmentioning
confidence: 99%
“…High-value compounds such as lignans, essential fatty acids, ferulic acid and phenols, tocopherols, anthocyanins, or ß-glucans are found in wheat, rice, corn, or barley wastes. After extraction, they are used in the food industry for the fortification of different types of food (bread, pasta, biscuits), as natural colorants, or in the pharmaceutical and cosmetic industries as a moisturizing agent [ 8 ]. The recovery of bioactive fractions by conventional and modern technologies and their further valorization in different industries is illustrated in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%